A multiple marker level-set method for simulation of deformable fluid particles. (September 2015) - Balcázar, Néstor; Lehmkuhl, Oriol; Rigola, Joaquim; Oliva, Assensi
Graphical abstract: Highlights: The algorithm is suitable for simulation of droplet and bubble dynamics without numerical coalescence. The numerical method is developed in the context of the conservative level-set method. The impact of a droplet with a liquid–liquid interface is studied. Simulations of binary drop collisions with bouncing outcome are presented. A simulation of buoyancy-driven bubbly flow is performed in a vertical pipe. Abstract: A novel multiple marker level-set method is introduced for Direct Numerical Simulation of deformable fluid particles (bubbles and droplets), which is integrated in a finite-volume framework on collocated unstructured grids. Each fluid particle is described by a separate level-set function, thus, different interfaces can be solved in the same control volume, avoiding artificial and potentially unphysical coalescence of fluid particles. Therefore, bubbles or droplets are able to approach each other closely, within the size of one grid cell, and can even collide. The proposed algorithm is developed in the context of the conservative level-set method, whereas, surface tension is modeled by the continuous surface force approach. The pressure–velocity coupling is solved by the fractional-step projection method. For validation of the proposed numerical method, the gravity-driven impact of a droplet on a liquid–liquid interface is studied; then, the binary droplet collision with bouncing outcome is examined, and finally, it is applied on simulation of gravity-driven bubbly flow in a vertical column.